Motivational Factors for Choosing ICT as an Elective Subject in Mathematics Education - Adhikari, Hom Kumari (KMC Research Journal, 2020)
This is an era of information and communication technology. Many students are highly interested in Information and Communications Technology (ICT) all over the world. Mathematics is often viewed as a critical enabling course that’s why ICT is necessary for higher level mathematics students. For this purpose, the curriculum of mathematics education of master’s levelhas adjusted ICT subject in mathematics course and most of the students choose ICT as an elective subject. Therefore, this study intended to explore the motivational factors for choosing ICT as an elective subject in mathematics along with gender perspective. This is descriptive survey research standing on post-positivist paradigm. The central department of education, mathematics education at Tribhuvan University was taken as the study area. Sixty- five students (53 boys, 12 girls)of master’s degree 4thsemester who had chosen ICT as an elective subject in mathematics education were selected as samples by simple random sampling method. The major tool of data collection was questionnaire and collected data were analyzed using simple descriptive statistics mean, percentage and inferential statistics t-test. The study found that the most popular motivational factor for choosing ICT as an elective subject in mathematics was their personal interest and the least popular reason was social factors for both boys and girls. This indicates that students were highly motivated towards ICT due to intrinsic motivation then after extrinsic motivation. In addition, there was no significant differences exist between boys and girls motivation in choosing ICT as an elective subject. Therefore, we should equally treat and encourage both boys and girls to study ICT as an elective subject in mathematics on which ICT helps to concretize mathematical concepts from abstraction.